Prevention of Cardiovascular Disease in Women - Saeed, Anum; Kampangkaew, June; Nambi, Vijay (Methodist DeBakey cardiovascular journal, 2017)
Cardiovascular diseases are the leading cause of morbidity and mortality among women worldwide. The pathophysiological basis of cardiovascular health among men and women is not identical. This leads to variable cardiovascular responses to stimulus and presentation of cardiovascular disease symptoms, both of which can have a direct effect on treatment outcomes. Traditionally, the enrollment of women in clinical trials has been minimal, resulting in a lack of gender-specific analysis of clinical trial data and, therefore, the absence of concrete risk factor assessment among women. However, scientific progress in the past decade has identified a spectrum of risk factors for cardiovascular diseases that may be specific to women. These risk factors, which may include menopause, hypertensive disease of pregnancy, and depression, confer additional risk in women besides the traditional risk factors. The current state of knowledge and awareness about these risk factors is suboptimal at this time. Therefore, although the treatment of cardiovascular diseases is similar in both genders, appropriate risk stratification may be limited in women compared to men. The purpose of this review is to describe the recent trends in identifying female-specific risk factors for cardiovascular diseases, their utility in risk stratification, and current pharmacological options for women with regard to cardiovascular disease prevention.